Impact of Setting up an "Endocarditis Team" on the Management of Infective Endocarditis. (16th July 2019) - Ruch, Yvon; Mazzucotelli, Jean-Philippe; Lefebvre, François; Martin, Aurélie; Lefebvre, Nicolas; Douiri, Nawal; Riegel, Philippe; Hoang Minh, Tam; Petit-Eisenmann, Hélène; Hansmann, Yves; Argemi, Xavier
Abstract: Background: Infective endocarditis (IE) remains a severe disease with a high mortality rate. Therefore, guidelines encourage the setup of a multidisciplinary group in reference centers. The present study evaluated the impact of this "Endocarditis Team" (ET). Methods: We conducted a monocentric observational study at Strasbourg University Hospital, Strasbourg, France, between 2012 and 2017. The primary end point was in-hospital mortality. Secondary end points were 6-month and 1-year mortality, surgery rate, time to surgical procedure, duration of effective antibiotic therapy, length of in-hospital stay, and sequelae. We also assessed predictors of in-hospital mortality. Results: We analyzed 391 episodes of IE. In the post-ET period, there was a nonsignificant decrease in in-hospital mortality (20.3% vs 14.7%, respectively; P = .27) and sequelae, along with a significant reduction in time to surgery (16.4 vs 10.3 days, respectively; P = .049), duration of antibiotic therapy (55.2 vs 47.2 days, respectively; P < .001), and length of in-hospital stay (40.6 vs 31.9 days, respectively; P < .01). In a multivariate analysis, the post-ET period was positively associated with survival (odds ratio, 0.45; 95% confidence interval, 0.20–0.96; P = .048). Conclusions: This multidisciplinary approach exerted a positive impact on the management of IE and should be considered in all hospitals managing IE. Abstract : The implementation of an 'Endocarditis Team' is recommended in reference centres for infective endocarditis. This study evaluated its impact and showed improvements on the management of this disease with a decrease in time to surgery and nonsignificant reduction in mortality.